2021
DOI: 10.1111/ppa.13475
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of pitaya stem rot caused by Gilbertella persicaria and its biological control by phyllosphere bacteria

Abstract: Pitaya is a succulent plant native to Central American countries, such as Mexico, and belongs to the Cactaceae family. It is cultivated in many countries, including Israel, Japan, Taiwan, and Vietnam (Yonemoto, 2009). It has been cultivated in the Okinawa Prefecture since the late 1980s and is now grown in Kagoshima and Miyazaki (Yonemoto, 2009). In Okinawa, mainly white (Hylocereus undatus), red (H. polyrhizus), yellow (Selenicereus megalanthus), and pink (H. undatus × H. ocaponis) pitaya plants are cultivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Wounds (5 × 5 mm) on fruit peels, bracts, and stems were made with sterile medical blades. e minimum wound depth was two mm (Taba et al, 2021). e suspension of G. persicaria GTC 2.3.1 spores (10 6 spores ml −1 ) was made with physiological saline from 7-day-old cultured slant agar.…”
Section: Pathogenicity Test For G Persicariamentioning
confidence: 99%
See 1 more Smart Citation
“…Wounds (5 × 5 mm) on fruit peels, bracts, and stems were made with sterile medical blades. e minimum wound depth was two mm (Taba et al, 2021). e suspension of G. persicaria GTC 2.3.1 spores (10 6 spores ml −1 ) was made with physiological saline from 7-day-old cultured slant agar.…”
Section: Pathogenicity Test For G Persicariamentioning
confidence: 99%
“…Sipiczki (2006) reported that the yeast strain Metschnikowia pulcherrima could inhibit many fungi, including G. persicaria. Recently, Taba et al (2021) showed that some strains of Bacillus subtilis could control the disease caused by G. persicaria on ex vivo pitaya stems with a similar efficiency to that of chemical treatments. rough the above studies, it can be seen that microbial antagonists were a potential approach to control G. persicaria.…”
Section: Introductionmentioning
confidence: 99%